Analisis Kelayakan Usahatani Padi Di Desa Sukatani, Kecamatan Kalianda - Dela Rosfita; Hasbi Andeska Maulana; Syahrudin; Aryan Ari Sepri YH (Prodi Agribisnis, 2026)
Rice remains the backbone of Indonesia's food security and continues to absorb a large share of rural household labor, yet the actual profitability of paddy cultivation at the farm level is rarely documented at the village scale. The shift toward mechanized harvesting, particularly the growing use of the combine harvester, has also begun to reshape the cost structure that rice farmers face at harvest time. This study sought to measure the cost, revenue, income, profit, and financial feasibility of rice farming among farmers in Sukatani Village, Kalianda Sub-district, South Lampung Regency. A quantitative descriptive method was used, drawing on primary field data recorded directly from farmer respondents during one planting season. The findings indicate that farmers spent an average explicit cost of IDR 761,500 and an implicit cost of IDR 14,655,625, bringing the total production cost to IDR 15,417,125. Average output reached 7,500 kilograms, sold at IDR 6,500 per kilogram, generating revenue of IDR 48,750,000, farm income of IDR 47,988,500, and profit of IDR 33,332,875. The R/C ratio obtained was 3.16, comfortably exceeding the feasibility threshold of one. This result suggests that rice farming practiced by farmers in Sukatani Village is financially sound and worth continuing.